Study of the possibility of using reagent number1 to remove and prevent deposits of paraffin in wells of Udmortia field - "Kamenshchikov, F A"; "Khodyreva, G V"; "Smirnov, Ya L" (1980)
Region number1 consists of nitrogen surfactants and wetting reagents, which are combined in a mixture of selective solvents. The density of the reagent is 0.92g/cm/sup 3/ at 15/sup 0/C, congealing temperature of the concentrated solution is below -40/sup 0/C, boiling temperature is 110/sup 0/C, viscosity is 25sP at 21/sup 0/C. The reagent is double-acting, being a solvent of deposited paraffin and an inhibitor of the deposition of paraffin. Laboratory and field studies at wells of Chutyrskiy field of Igrinskiy oil and gas administration showed that Region number1 is not effective as a solvent of pitch and paraffin deposits. It can be used as an inhibitor to prevent deposits of paraffin. Its most favorable concentration in oil is 0.5%.
Keywords: "02 PETROLEUM"; "03 NATURAL GAS"; "PARAFFIN"; "CONTROL"; "WELLS"; "DEWAXING"; "NITROGEN"; "PITCHES"; "REAGENTS"; "SEPARATION PROCESSES"; "SOLVENTS"; "SURFACTANTS"; "WETTING AGENTS"; "ALKANES"; "ELEMENTS"; "HYDROCARBONS"; "NONMETALS"; "ORGANIC COMPOUNDS"; "OTHER ORGANIC COMPOUNDS"; "WAXES"; "020300* - Petroleum- Drilling & Production"; "030300 - Natural Gas- Drilling, Production, & Processing"